Phenolic content of Sicilian virgin olive oils and their effect on MG-63 human osteoblastic cell proliferation - O. García-Martínez; G. Mazzaglia; A. Sánchez-Ortiz; F. M. Ocaña-Peinado; A. Rivas (Grasas y Aceites, 2014)
The aim of this study was, first, to investigate the influence of olive variety and elevation of orchards on the phenolic compound content of Sicilian virgin olive oils (VOOs) and, second, to investigate the effects of VOO phenolic extracts on osteoblast cell growth using the human MG-63 osteosarcoma cell line. Olive oil phenolic content and its effect on human osteosarcoma cell proliferation varied according to the type of cultivar and the grove altitude. This variation was also observed within the same type of cultivar. This observation demonstrates that the cultivar and the grove location can significantly affect the chemical composition and bioactivity of virgin olive oil. Although this study supports the hypothesis that virgin olive oil phenolic fractions exert a beneficial effect on bone health, further studies assessing the in vivo accessibility of virgin olive oil phenolic compounds to osteoblast cells should be carried out.